2015
DOI: 10.1182/blood-2014-09-598268
|View full text |Cite
|
Sign up to set email alerts
|

Affinity of FVIII-specific antibodies reveals major differences between neutralizing and nonneutralizing antibodies in humans

Abstract: Key Points• A new technology is presented to assess apparent affinities of FVIII-specific antibodies, differentiated for isotypes and IgG subclasses.• Affinities of FVIII-specific antibodies in patients with FVIII inhibitors are up to 100-fold higher than in patients without inhibitors.Recently, we reported that distinct immunoglobulin (Ig) isotypes and IgG subclasses of factor VIII (FVIII)-specific antibodies are found in different cohorts of patients with hemophilia A and in healthy individuals. Prompted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(139 citation statements)
references
References 29 publications
(39 reference statements)
5
127
0
7
Order By: Relevance
“…Antibodies were analyzed by using fully validated semiquantitative, directbinding enzyme-linked immunosorbent assays (ELISAs) as described in Whelan et al 6 Details of the validation procedure as well as details of the cutoff determination and the sensitivity of the ELISAs are provided in Whelan et al 6 and Hofbauer et al 7 Initially, all samples were screened in a 1:20 dilution for FVIII-binding IgG antibodies. Samples that tested positive were characterized for titers of FVIIIbinding IgG subclasses and apparent affinities.…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies were analyzed by using fully validated semiquantitative, directbinding enzyme-linked immunosorbent assays (ELISAs) as described in Whelan et al 6 Details of the validation procedure as well as details of the cutoff determination and the sensitivity of the ELISAs are provided in Whelan et al 6 and Hofbauer et al 7 Initially, all samples were screened in a 1:20 dilution for FVIII-binding IgG antibodies. Samples that tested positive were characterized for titers of FVIIIbinding IgG subclasses and apparent affinities.…”
Section: Methodsmentioning
confidence: 99%
“…In previous reports, NNA prevalence ranged from 2% to 3% in healthy individuals 16,18,21,24 and from 12.2% to 53.8% in patients with hemophilia A. [13][14][15][16][17][18][19][20][21][22]24,25,29,30 Several factors, particularly that all previous studies predominantly included patients with multiple transfusions, explain this large variation and the gaps in knowledge about their potential clinical role.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22]24,25,29,30 Several factors, particularly that all previous studies predominantly included patients with multiple transfusions, explain this large variation and the gaps in knowledge about their potential clinical role. For instance, the intron 22 inversion of FVIII mutation was associated with an increased frequency of NNAs in patients who had had multiple transfusions in 1 study 29 that was not confirmed in another study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This raises the intriguing possibility that dangerous antibodies might be detected before bleeding occurs. Detecting the risk of bleeding before it occurs will require assay (s) that better measure the risk of bleeding.…”
mentioning
confidence: 99%